TiO2 thin film photocatalyst with solar energy in textile industrial wastewater treatment / Nur Fadzeelah Abu Kassim - Abu Kassim, Nur Fadzeelah (2007)
Among the new methods of treatment of wastewater containing dyes is photocatalytic degradation in solutions illuminated with UV irradiation containing titanium dioxide (TiO2) as suitable photocatalyst. Photocatalytic degradation is gaining importance in the area of wastewater treatment, mainly in textile industry. A serpentine solar flow photocatalytic reactor was developed for this purpose. This kind of reactor achieved a uniform flow distribution and irradiation of the entire photocatalyst surface TiO2 thin films photocatalyst supported on the stainless steel 304 plate as a substrate. This photocatalyst was prepared using sol-gel dip coating method from the system containing alkoxide solutions with two polyethylene glycol (PEG) molecular weight, PEG400 and PEG2000. The prepared photocatalyst was characterized using X-Ray Diffractometer (XRD), Thermo Gravimetric Analyzer (TGA) and Scanning Electron Micrograph (SEM). Five experimental conditions were studied to investigate the decreasing of Chemical Oxygen Demand (COD) on the solar photocatalytic activity of textile industry wastewater, i.e. photolysis (without TiO2) , TiO2 thin film without solar, TiO2 thin film, TiO2 thin film with aeration and TiO2 powder (suspended system). The transition from amorphous to crystalline phase (anatase) was observed obviously after calcinations for both PEG molecular weights. However, PEG2000 is more photoreactive than PEG400 due to high peak intensity formation. SEM results showed that the spherical pores and macroporous structure formed using PEG2000. The larger molecular weight of PEG, the higher possibility of forming the porous TiO2 thin films. From the photocatalysis experiments, sample TiO2 thin film with aeration revealed the highest COD removal, which is 17.13% compared with another four samples after four hours irradiation time. Thus, dissolved oxygen is significantly affected on the photocatalytic degradation. Finally, photocatalysis using solar had successfully removed 58.92% of SS (Suspended Solid), 17.13% of COD and 4.68% of TOC (Total Organic Carbon).